Manifestation's Minimization of Social Exclusion In Ukraine Based on Overcoming Dysfunctionality of the Socio-Economic Systems Regulation - Maria Karpiak; Nazariy Popadynets; Viktoria Bondarenko; Oxana Nazarkevych (Vasyl Stefanyk Precarpathian National University, 2023)
Achievement of balanced development of socio-economic systems of different levels lies in the plane of effective regulation of processes arising as a result of the action of various factors associated with negative phenomena of both an economic and social nature. Ensuring effective regulatory influence on the part of state and regional authorities is a guarantee of sustainable socio-economic development of the state and its regions, reducing interregional disparities, increasing the investment attractiveness of territories, preventing complications on a political, economic, and interethnic basis. This, in turn, is the basis of national state policy, as well as regional policy as its integral component. The modern dynamism of socio-economic development poses new challenges to the state due to the need to counteract the negative effects of the incessant transformations. We consider the strengthening of inequality and processes of social polarization caused by changes in the social structure of society to be the most striking of them. These changes have resulted today in the spread of such a negative social phenomenon as social exclusion. The problem of social exclusion in Ukraine and its regions is primarily related to the dysfunctionality of the processes of regulation of the main spheres of ensuring citizens' livelihoods, in particular, the spheres of employment, wages, social guarantees and the availability of social services. In addition, the significant risk for individuals to fall into the category of socially excluded today is caused by the presence of other destabilizing factors of an economic nature. These factors include the presence of significant imbalances in the labor market, in particular, a high level of unemployment and a reduction in the number of jobs, a significant level of poverty, including among the working population, the risk of not getting a job in accordance with the acquired qualification level and other factors that are especially threatening for the preservation and development of the human potential of the state.